Achieving Scalability in Project Based Learning through a Low-Code Platform - Fernandes, João Paulo; Araújo, Ricardo; Zenha-Rela, Mário (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
Defining an adequate project for a Software Engineering course is a challenging endeavour. Such a project must simulate as faithfully as possible a real industrial project, while accounting, e.g., for: i) the natural lack of experience of the students, ii) their constraints to full-time dedication, and iii) reasonable effort required from the instructors. Additionally, while having a real client from industry may contribute to a more realistic experience, the project itself must be challenging enough to motivate the client while still not unduly burden the students.We report on our experience and share our insights from adopting a state-of-the-art low-code software development platform as the core technology for project-based learning -with a real clientin a one-semester software engineering course. We had to handle i) a large class (200+ students), while providing ii) individual assessment iii) for students from very different backgrounds (majoring in three different topics). While we believe i) and ii) are recurrent, iii) poses a significant challenge in the establishment of a fair pedagogic context.We assess the merit of the experience taking as proxy: i) the students' individual and group performance, assessed both by the instructors and the client, and ii) the results of the course's standard institutional pedagogical survey. We have found evidence that the designed project created an even playing field for students from different backgrounds, while being manageable for the instructors and rewarding for the client.